2020 Fifth International Conference on Informatics and Computing (ICIC) 2020
DOI: 10.1109/icic50835.2020.9288597
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of System and Service Qualities on Customer Loyalty in Acceptance of E-Marketplace

Abstract: The effect of the perceived mobility and the provider reputation towards the usage continuance of the personal cloud storage

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 29 publications
3
7
0
Order By: Relevance
“…Adapted from [12], Satisfaction was defined as "the end user's affective attitude towards a MOOCs application. Several studies showed the significantly effect of Confirmation on Satisfaction [2], [3], [4], [5], [6], [7]). Khaled [2] and Day [4] conducted research on user acceptance of MOOCs, Prasetya [3], Prasetya [5], and Widiantoro [7] examine the adoption of eLearning systems on young people, and Prasetya [6] studied on consumer acceptance on e-marketplace.…”
Section: Confirmation On Satisfaction and Perceived Usefulnessmentioning
confidence: 99%
See 4 more Smart Citations
“…Adapted from [12], Satisfaction was defined as "the end user's affective attitude towards a MOOCs application. Several studies showed the significantly effect of Confirmation on Satisfaction [2], [3], [4], [5], [6], [7]). Khaled [2] and Day [4] conducted research on user acceptance of MOOCs, Prasetya [3], Prasetya [5], and Widiantoro [7] examine the adoption of eLearning systems on young people, and Prasetya [6] studied on consumer acceptance on e-marketplace.…”
Section: Confirmation On Satisfaction and Perceived Usefulnessmentioning
confidence: 99%
“…Furthermore, other studies on MOOCs and e-learning adoption stated that confirmation has direct effect on PU ([2], [6], [7]) and Continue Intention [3].…”
Section: Confirmation On Satisfaction and Perceived Usefulnessmentioning
confidence: 99%
See 3 more Smart Citations